Analysis of Sound Translation of Indonesian Names in The Chinese Newspaper “Indonesian Daily” (Yinni Xingzhou Ribao) - Rosella Hasyim; Pauw Budianto (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2021)
In the process of learning Mandarin, Indonesian names are often found transliterated into Mandarin. In this research, the writer will discuss about Indonesian names which are transliterated into Mandarin. This study will discuss the classification of the translation of the sounds of Indonesian names and the findings in translating the sounds of Indonesian names into Chinese which are presented in the Chinese newspaper